Development of Millet and Soybean Based Ready-to-Eat Snack Food Chakli - Deshpande, Sumedha; Jha, Krishna (Journal of Agricultural Engineering, 2015)
Ready- to- eat snack food chakli was prepared using sorghum, pearl millet and finger millet with defatted soy-flour and medium fat soy flour. Developed product was analysed for nutritional quality, acceptability and textural profile. Incorporation of 50% millet and 15-20% DFSF/MFSF was acceptable. Nutritional analysis revealed that 20% soybean incorporation in the form of defatted soy-flour and medium fat soy-flour enhanced the protein content up to 75-80% and 59-64%, respectively compared to traditional product. Textural analysis showed that incorporation of finger millet with DFSF required higher bending strength.